Peran Sistem Akreditasi Dalam Meningkatkan Produktivitas di Lembaga Pendidikan - Maulana, Muhamad Iqbal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The aim of this research is to find out the role of the accreditation system in increasing productivity in schools. The school accreditation system serves as a guide in providing a comprehensive assessment of the eligibility of a program in educational institutions which can provide ranking feasibility and provide information about the eligibility of schools/madrasas which are implemented based on the National Education Standards. This research method is to use a literature review study. The type of research used is descriptive. Researchers collected data by conducting a study of theories relevant to the discussion, namely the role of the accreditation system in increasing productivity in educational institutions. This study conducts a critical review of the results of previous studies to be compared with the latest studies to obtain new research results that are supported by theories that can be adopted from books, documents, papers, or published research results. The results in this study indicate that the school accreditation system is very important in increasing the productivity of institutions by carrying out various efforts including providing assistance on the effectiveness of the performance of school principals, staff teachers in carrying out management processes in educational institutions. With the existence of a school accreditation system, it is hoped that educational institutions will continue to make improvements to school management in order to achieve the ideal quality level of educational institutions in accordance with national education standards.